Thyroid dysfunction in chronic obstructive pulmonary disease - Subedi, Bhusan Kumar; Shrestha, Surendra Lal; Nagarkot, Sujata; Subedi, Shova; Twanabasu, Sajal; Maskey, Sujina (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Chronic obstructive pulmonary disease (COPD) is one of the major causes of morbidity and mortality in the world, leading to worsening of quality of life. Other comorbidities have significant impact on the disease course. Thyroid dysfunctions might be associated with frequent COPD exacerbations. Identifying such an underestimated comorbidity is important for its early addressing and delaying progression of COPD complications.Method: This was a cross-sectional descriptive study done among COPD patients attending at Bir hospital from March 2021 to April 2022. A total of 75 patients fulfilling inclusion criteria were interviewed and underwent clinical as well as laboratory investigations. Data were entered and analyzed using the statistical software IBM-SPSS version 22.Result: The prevalence of thyroid dysfunction ranged from 2(2.7%) in stage A to 22(29.3%) in stage D. On further analysis, prevalence of hypothyroidism 2(2.7%) in stage A to 14(18.7%) in stage D. Hypothyroidism was found more common in COPD than hyperthyroidism 0(0%) hyperthyroidism in stage A to 8(10.7%) in stage D). The prevalence of thyroid dysfunction with no exacerbations was found to be 0(0%) whereas those with exacerbations but not requiring hospitalization accounted for 7(9.3%). Similarly, 10(13.3%) required hospitalization and 18(24%) had 2 or more exacerbations.Conclusion: Our study has shown that prevalence of thyroid dysfunction is common among COPD patients. Moreover, COPD patients with thyroid dysfunction suffer more from exacerbation states. Early identification and treatment of thyroid dysfunction seems quite beneficial to reduce the frequency of exacerbations and enhance the quality of life of COPD patient.